Using qualitative research to facilitate the interpretation of quantitative results from a discrete choice experiment: insights from a survey in elderly ophthalmologic patients - Vennedey, Vera (Patient Prefer Adherence, 2016)
BACKGROUND: Age-related macular degeneration (AMD) is the leading cause of visual impairment and blindness in industrialized countries. Currently, mainly three treatment options are available, which are all intravitreal injections, but differ with regard to the frequency of injections needed, their approval status, and cost. This study aims to estimate patients’ preferences for characteristics of treatment options for neovascular AMD. METHODS: An interviewer-assisted discrete choice experiment was conducted among patients suffering from AMD treated with intravitreal injections. A Bayesian efficient design was used for the development of 12 choice tasks. In each task patients indicated their preference for one out of two treatment scenarios described by the attributes: side effects, approval status, effect on visual function, injection and monitoring frequency. While answering the choice tasks, patients were asked to think aloud and explain the reasons for choosing or rejecting specific characteristics. Quantitative data were analyzed with a mixed multinomial logit model. RESULTS: Eighty-six patients completed the questionnaire. Patients significantly preferred treatments that improve visual function, are approved, are administered in a pro re nata regimen (as needed), and are accompanied by bimonthly monitoring. Patients significantly disliked less frequent monitoring visits (every 4 months) and explained this was due to fear of deterioration being left unnoticed, and in turn experiencing disease deterioration. Significant preference heterogeneity was found for all levels except for bimonthly monitoring visits and severe, rare eye-related side effects. Patients gave clear explanations of their individual preferences during the interviews. CONCLUSION: Significant preference trends were discernible for the overall sample, despite the preference heterogeneity for most treatment characteristics. Patients like to be monitored and treated regularly, but not too frequently or infrequently. The results of our qualitative research facilitated the interpretation of the quantitative data collected in this study.